Perfluoroalkyl acids in surface sediments of the East China Sea. (December 2017) - Wang, Qian-Wen; Yang, Gui-Peng; Zhang, Ze-Ming; Jian, Shan
Abstract: The occurrence of 17 target PFAA analytes was determined in surface sediments ( n = 37) of the East China Sea and potential influencing factors were examined. ΣPFAAs ranged from 0.41 ng/g dw to 3.06 ng/g dw, with perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) as the most abundant perfluorocarboxylic acid and perfluoroalkyl sulfonate, respectively. PFAAs in the sediments were strongly influenced by terrigenous input. Analysis of the relationship between dynamic influence factors and PFAA concentrations showed that the characteristics of PFAA distribution were rather complex. ΣPFAA concentrations and TOC were positively correlated ( p < 0.0001). Circumfluence also influenced the whole PFAA distribution and seasonal variation. In addition, correlation analysis suggested that log K oc values increased with increasing perfluoroalkyl chain length. Given the rapid economic development of eastern coastal cities of China, the environmental hazards of land source pollution cannot be ignored. Graphical abstract: Highlights: PFAAs widely occurred in the sediments of the East China Sea. PFAAs in the sediments were strongly influenced by terrigenous input. Dynamic influence factors played an important role in the distribution of PFAAs. Circumfluence influenced the whole PFAA distribution and seasonal variation. Log K oc values increased with increasing perfluoroalkyl chain length. Abstract : Spatial distributions and dynamic influence factors of PFAAs in surface sediments of the East China Sea were investigated.